Perawatan Mesin Diesel Generator Pada Kapal KN.SAR SADEWA 231 - Lukas Kristianto; Waris Wibowo; Ningrum Astriawati; Nanang Kristiawan (Indonesian Society of Applied Science, 2022)
A generator or alternator is a copper coil or coil consisting of a stator (static coil) and a rotor (rotating coil). The main function of the generator on board is to supply the electrical power needs on board. One of the disturbances that occur in generators is often the heat of the generator (overheating) and also the absence of electric voltage on the generator. The purpose of this study is to optimize maintenance on the generator maintenance system on KN ships. SAR SADEWA 231. This research is qualitative descriptive research. This research was on the engine of the KN SAR Sadewa 231 ship belonging to the Semarang Search and Rescue (SAR) Search and Rescue Office. The results showed that the generator on the main engine of the KN Ship. SAR SADEWA 231 uses an Alternating current (AC) generator power generation system. The implementation of maintenance of the generator system on the ship is good. The generator system parts that are treated include the stater dynamo, alternator, fuel filter, air filter, cooler, nozzle, bosh pump, turbocharge, muffler, and main board switch.